2017
DOI: 10.1016/j.atherosclerosis.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide attenuates calcification of vascular smooth muscle cells via KEAP1/NRF2/NQO1 activation

Abstract: Sulfide attenuates CPP-induced VSMC calcification in vitro via the KEAP1-NRF2 redox sensing/stress response system by enhancing NQO1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 47 publications
2
74
0
4
Order By: Relevance
“…In vivo and in vitro evidence has shown that oxidation and oxidation products are widely present in degenerated intervertebral discs . Studies have reported that oxidative stress may increase the incidence of apoptosis through the mitochondria‐dependent pathway in various cell types; in addition, reactive oxygen species and oxidative stress products have been shown to increase ectopic calcification formation in cardiovascular cells . Han et al reported that oxidative stress may induce apoptosis and promote calcification in disc cartilage endplate cells .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro evidence has shown that oxidation and oxidation products are widely present in degenerated intervertebral discs . Studies have reported that oxidative stress may increase the incidence of apoptosis through the mitochondria‐dependent pathway in various cell types; in addition, reactive oxygen species and oxidative stress products have been shown to increase ectopic calcification formation in cardiovascular cells . Han et al reported that oxidative stress may induce apoptosis and promote calcification in disc cartilage endplate cells .…”
Section: Discussionmentioning
confidence: 99%
“…A well known therapeutic attribute of MnPs is their ability to protect healthy cells and increase susceptibility of malignant cells to radiation therapy. This process has been attributed in part to increased H 2 O 2 which, in a process catalyzed by MnP, oxidizes signaling proteins such as NFκB [4,10,31]. Our results suggest that persulfides produced by MnP oxidation of H 2 S could have a similar effect with the added bonus of direct oxidant scavenging by persulfides.…”
Section: Antioxidant Function Of Mnp-generated Polysulfidesmentioning
confidence: 64%
“…CPP2-induced calcification of VSMCs was largely ameliorated by the H 2 S-donor NaHS via activation of the KEAP1/NRF2/NQO1 pathway (Aghagolzadeh et al, 2017).…”
Section: H 2 S In Vascular Calcificationmentioning
confidence: 96%